Pembuatan Kulit Biosintetis dari Nata De Banana menggunakan Polyurethane dan Anti Bakterial Chitosan - Nurmila, Nurmila; Rahmahwati, Cut Aja; Elwina, Elwina (Politeknik Negeri Lhokseumawe, 2025)
Organic synthetic leather is engineered leather created with raw materials that can be found around the human environment in the form of fruits or fruit peels which have high fiber so that they can deal with organic waste, with organic synthetic leather the population of animals killed for their skins reduced so as to maintain the survival of animals. This study aims to determine the effect of the addition of polyurethane (PU) and chitosan on the characteristics of the resulting leather. With variation (Polyurethane A) 2 : 1 (Polyurethane B), namely 15 mL, 30 mL, 45 mL, 60 mL, 75 mL and chitosan 2 g, 4 g, 6 g, 8 g, 10 g. The addition of PU affects the elasticity and hardness of the final leather product and chitosan has the effect of inhibiting bacterial growth and fungus on synthetic leather. The organoleptic test for all synthetic leather does not meet SNI standards. Based on the results of anti-bacterial testing (colony counter) there were the highest bacteria in the lowest chitosan variation, namely 2 grams and the lowest bacteria in the highest chitosan variation, namely 10 grams. The result of the tensile strength test is that the highest tensile strength value is produced by PU (2:1) at 50:25 ml polyurethane volume of 3.432 MPa with 21.36% elongation and the lowest tensile strength value is produced by PU (2:1) at 15 volume : 8 mL of 16.181 MPa elongation 21.42%.